Micrometeorological environments and biodiversity in a closed forest and at a tree-fall gap in central Amazonia. - Tsuchiya, Akio; Tanaka, Akira (Ciência Florestal, 2008)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –> Micrometeorological parameters were measured in a closed forest (CF) and at a tree-fall gap (LG) near Novo Aripuanã, AM, along the Madeira River in dry season (August to September 2003) and rainy season (March 2004), and were compared to the number of species per family and the number of seedlings obtained from forest inventory. The daily averages of net radiation (W/m2) between CF and LG were 9.5:168.0 during dry season and 3.6:125.9 during rainy season, and these averages were influenced by the difference in shortwave radiation between the sites (CFPourouma, Parkia, Tachigalia, and Orbignya, meanwhile genera peculiar to closed forests (Protium, Chrysophyllum, Micropholis) were also found.